FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI DI WILAYAH KERJA UPTD PUSKESMAS RASUAN - Sulastri, Sulastri; Mastina, Mastina; ernawati, wahyu (IMJ (Indonesian Midwifery Journal), 2023)
Hypertensive disorders in pregnancy are defined as vascular abnormalities occurring before, during, or after childbirth. Cases of hypertension during pregnancy are still common in society and remain one of the leading causes of maternal mortality. While maternal mortality rates have decreased, they are still far from the Sustainable Development Goals (SDGs) target for 2021. This study employed a quantitative approach with a cross-sectional design. The population in this study consisted of 596 mothers registered in community health posts (posyandu) within the Working Area of  UPTD of Rasuan Community Health Center in East Oku Regency in 2023. The research results showed a significant relationship of knowledge (p value= 0.002), nutritional status (p value= 0.002), and obesity (p value= 0.000) with hypertension during pregnancy in UPTD of Rasuan Community Health Center in 2023. It is expected that the findings of this research can contribute to the development and enhancement of hypertension prevention during pregnancy.